2021
DOI: 10.1364/boe.443343
|View full text |Cite|
|
Sign up to set email alerts
|

Deep convolutional neural network-based scatterer density and resolution estimators in optical coherence tomography

Abstract: We present deep convolutional neural network (DCNN)-based estimators of the tissue scatterer density (SD), lateral and axial resolutions, signal-to-noise ratio (SNR), and effective number of scatterers (ENS, the number of scatterers within a resolution volume). The estimators analyze the speckle pattern of an optical coherence tomography (OCT) image in estimating these parameters. The DCNN is trained by a large number (1,280,000) of image patches that are fully numerically generated in OCT imaging simulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Summary of spatial correlation distance characteristics of three noise types and the OCT signal. In the new noise model, each type of noise has different spatial correlation properties, whereas these properties [18] are identical for all noise types in the old noise model. In this study, we consider scanning OCT, rather than a full-field OCT. Because each A-line of the scanning OCT is acquired at a different time, none of the three noise types have spatial correlation along the lateral direction.…”
Section: Noise Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of spatial correlation distance characteristics of three noise types and the OCT signal. In the new noise model, each type of noise has different spatial correlation properties, whereas these properties [18] are identical for all noise types in the old noise model. In this study, we consider scanning OCT, rather than a full-field OCT. Because each A-line of the scanning OCT is acquired at a different time, none of the three noise types have spatial correlation along the lateral direction.…”
Section: Noise Modelmentioning
confidence: 99%
“…Speckle contrast was expected to aid in estimating the number of scatterers in the resolution volume (ENS), while resolution volume could be derived from estimated resolutions (as discussed in Section 4.3 of Ref. [18]). This principle could work effectively if speckle contrast were sensitive to ENS, particularly for small ENS values However, we found that our SDE could function not only in this regime but also for cases with large ENS values.…”
Section: Open Issue: Physical Mechanism Used In the Sdementioning
confidence: 99%
See 1 more Smart Citation
“…In our JM-OCT, we additionally use scatterer density imaging achieved by a neural-network-based scatterer density estimator [65]. This estimator is based on a convolutional neural network trained by using numerically generated OCT images.…”
Section: E Intensity Oct Attenuation Coefficient and Scatterer Densitymentioning
confidence: 99%
“…In addition to the D-OCT analysis, Seesan et al recently applied neural-network-based scatterer-density analysis to the JM-OCT signal [65]. This revealed a temporal reduction in the scatterer density after the spheroid was extracted from the culturing environment as shown in Fig.…”
Section: E Ex Vivo and In Vitro Tissue Imagingmentioning
confidence: 99%